MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI MELALUI PEMBELAJARAN KOOPERATIF MODEL EXAMPLE NON EXAMPLE POKOK BAHASAN PERILAKU KONSUMEN DAN PRODUSEN DI KELAS X IS-1 SMA NEGERI 2 LUBUK PAKAM TAHUN PELAJARAN 2019/2020 - Helmi Pangaribuan (Universitas Negeri Medan, 2021)
This study aims to determine the increase in student learning outcomes by using an example non-example cooperative learning model in Economics class X IS-1 SMA Negeri 2 Lubuk Pakam in the 2019/2020 academic year. The research method is classroom action research and the research subject is class X IS-1. The class studied consisted of 34 students. Based on the learning outcomes of the first cycle, the average result was 72.5 while in the second cycle, there was an increase in the student's average score to 86.65. In this study, the data obtained from the criteria for learning completeness in cycle I with a percentage of 50% after the implementation of cycle II increased student learning outcomes to 100%. Thus learning in this study can be said to have been completed. Based on the results of the research above, it can be concluded that learning using the cooperative learning model type example non example on the subject matter of the origin of human distribution in the Indonesian archipelago in class X IS-1 SMA Negeri 2 Lubuk Pakam in the 2019/2020 academic year has increased student learning outcomes .